2014
DOI: 10.1074/jbc.m114.558262
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rho GDP Dissociation Inhibitor α in Control of Epithelial Sodium Channel (ENaC)-mediated Sodium Reabsorption

Abstract: Background: RhoGDI␣ regulates activity of Rho family small GTPases, which are recognized as important modulators of ENaC. Results: RhoGDI␣ modulates Rac1 activity and partially participates in the effects of EGF on ENaC in the cortical collecting ducts. Conclusion: RhoGDI␣ controls ENaC expression and activity via Rac1. Significance: A novel mechanism for RhoGDI␣-dependent regulation of ENaC is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…We also investigated the involvement of Rac1 in 4% saltinduced excessive ENaC activity and found that a high-salt diet decreased the abundance of RhoGDI␣ in CDs of SS rats. Ex vivo studies revealed that low RhoGDI␣ levels augmented the bioavailability of Rac1 and activated ENaC-mediated Na ϩ reabsorption (37,62). These findings indicate that a high-salt diet leads to renal MR activation and RhoGDI␣ downregulation, which increase ENaC-mediated sodium reabsorption via higher Rac1 activity.…”
Section: F136mentioning
confidence: 86%
“…We also investigated the involvement of Rac1 in 4% saltinduced excessive ENaC activity and found that a high-salt diet decreased the abundance of RhoGDI␣ in CDs of SS rats. Ex vivo studies revealed that low RhoGDI␣ levels augmented the bioavailability of Rac1 and activated ENaC-mediated Na ϩ reabsorption (37,62). These findings indicate that a high-salt diet leads to renal MR activation and RhoGDI␣ downregulation, which increase ENaC-mediated sodium reabsorption via higher Rac1 activity.…”
Section: F136mentioning
confidence: 86%
“…For example, we observed that expanded human airway stem cell-derived epithelia gradually lose CFTR-mediated chloride and ENaC-mediated sodium conductance, but interestingly they do maintain transepithelial resistance and differentiation potential. In fact, several studies (Pavlov et al, 2014; Staruschenko et al, 2004) have demonstrated the negative effect of ROCK inhibitor Y27632 and EGF on ENaC activity, which may explain the gradual decrease in ENaC-mediated sodium conductance in cells expanded in the presence of Y27632 and EGF. Partial loss of cellular physiological function in in vitro culture systems may be more common than previously recognized and may be tissue-specific and function-specific.…”
Section: Discussionmentioning
confidence: 99%
“…14 Salt-induced activation of Rac1-MR pathway in distal tubules develops salt-sensitive hypertension, 12 through augmented tubular sodium reabsorption induced by increased epithelial sodium channel (ENaC) activity. 15 Notably, the absence of severe renal injury in diabetic mice, most of which are normotensive, poses an obstacle to experimental studies related to DKD. 16 Chronic progression of DKD, which is often associated with hypertension, brings a gradual decrease in the renal function.…”
mentioning
confidence: 99%
“…14 Salt-induced activation of Rac1-MR pathway in distal tubules develops salt-sensitive hypertension, 12 through augmented tubular sodium reabsorption induced by increased epithelial sodium channel (ENaC) activity. 15…”
mentioning
confidence: 99%